Time-Varying Parameter Identification of Bridges Subject to Moving Vehicles Using Ridge Extraction Based on Empirical Wavelet Transform - Li, Jiantao; Guo, Jian; Zhu, Xinqun (International journal of structural stability and dynamics, 2021)
For a vehicle moving over a bridge, the vehicle-bridge interaction (VBI) embraces the time-varying modal parameters of the system. The identification of non-stationary characteristics of bridge responses due to moving vehicle load is important and remains a challenging task. A new method based on the improved empirical wavelet transform (EWT) along with ridge detection of signals in time-frequency representation (TFR) is proposed to estimate the instantaneous frequencies (IFs) of the bridge. Numerical studies are conducted using a VBI model to investigate the time-varying characteristics of the system. The effects of the measurement noise, road surface roughness and structural damage on the bridge IFs are investigated. Finally, the dynamic responses of an in-situ cable-stayed bridge subjected to a passing vehicle are analyzed to further explore the time varying characteristics of the VBI system. Numerical and experimental studies demonstrate the feasibility and effectiveness of the proposed method on the IF estimation. The identified IFs reveal important time-varying characteristics of the bridge dynamics that is significant to evaluating the actual performance of operational bridges in operation and may be used for structural health assessment.